Near‐surface temperature gradient in a coastal upwelling regime. Issue 8 (11th August 2014) - Maske, H.; Ochoa, J.; Almeda‐Jauregui, C. O.; Ruiz‐de la Torre, M. C.; Cruz‐López, R.; Villegas‐Mendoza, J. R.
Abstract In oceanography, a near homogeneous mixed layer extending from the surface to a seasonal thermocline is a common conceptual basis in physics, chemistry, and biology. In a coastal upwelling region 3 km off the coast in the Mexican Pacific, we measured vertical density gradients with a free‐rising CTD and temperature gradients with thermographs at 1, 3, and 5 m depths logging every 5 min during more than a year. No significant salinity gradient was observed down to 10 m depth, and the CTD temperature and density gradients showed no pronounced discontinuity that would suggest a near‐surface mixed layer. Thermographs generally logged decreasing temperature with depth with gradients higher than 0.2 K m−1 more than half of the time in the summer between 1 and 3 m, 3 and 5 m and in the winter between 1 and 3 m. Some negative temperature gradients were present and gradients were generally highly variable in time with high peaks lasting fractions of hours to hours. These temporal changes were too rapid to be explained by local heating or cooling. The pattern of positive and negative peaks might be explained by vertical stacks of water layers of different temperatures and different horizontal drift vectors. The observed near‐surface gradient has implications for turbulent wind energy transfer, vertical exchange of dissolved and particulate water constituents, the interpretation of remotely sensed SST, and horizontal wind‐induced transport.